Effects of Hot Water and NaOH Pretreatment on Fibre Diameter and Acoustic Properties of EFB Cement Board - Mohd Najib, Amalia Manarina; Samsudin, Emedya Murniwaty (Recent Trends in Civil Engineering and Built Environment, 2024)
Residue and residual oil on oil palm empty fruit bunch (EFB) fibres must be removed using appropriate pre-treatment before they can be utilised in the fabrication of EFB cement board. Pre-treatment resulting in variations in diameter and affects the acoustical performance of fibre composites. The purpose of this research is to define the effects of different treatment methods on the fibres diameter and to determine and compare the sound absorption performance of EFB Cement Board based on different treatment methods. The diameter of the fibres are measured by average using 5 strands of each treatment. Meanwhile, the cement board’s sound absorption is measured using an impedance tube. Pretreatment of fibres are accomplished by the use of two distinct methods which are Sodium Hydroxide (NaOH) at concentrations of 0%, 2%, 4%, and 6%, and hot water treatment at temperatures ranging from 50°C to 60°C and 70°C. In both pretreatments, 3 hours of soaking time will be maintained. The diameter of strand is measured using digital microscope which is Scanning Electron Microscope (SEM), and the sound absorption of the EFB were determined in accordance with ISO10534-2:2001. Results shows that the untreated average data was 472.93 μm, whereas the hot water pretreatment obtained the thinnest strand diameter at 417.46 μm at 50°C, and the 2 % NaOH obtained the thinnest at 384.31m. The maximum value sound absorption for NaOH pretreatment was obtained with 6 % NaOH treated 0.586 and for hot water pretreatment 0.584 with temperature 70°C, both at 1600Hz, compared to the highest value sound absorption for untreated 0.486 at 1400 Hz. The average diameter of the untreated was 472.93μm, whereas the thinner diameter of the NaOH pretreatment was 417.46 μm at 50°C, while the 2 % NaOH was 384.31μm. Based on the comparison results, it is possible to conclude that NaOH pretreatment was superior to hot water pretreatment in terms of reducing fibre diameter. As a result, the NaOH pretreatment is suggested when treating EFB fibre to remove the outer layer of the strand.